The Effect of Corporate Governance Mechanisms on Company Value - Fadilla, Pasha; Arifin, Zaenal (Selekta Manajemen: Jurnal Mahasiswa Bisnis & Manajemen, 2022)
Corporate governance is a central issue used in measuring the capacity and value of a company. This study aims to analyze the effect of corporate governance mechanics on the value of a company that is included in the LQ-45 shares listed on the Indonesia Stock Exchange for the 2018–2020 period. Quantitative research design with a descriptive approach Purposive sampling was used to collect the data, which resulted in a total of 101 data points. Corporate governance indicators and company values include the Board of Independent Commissioners, Institutional Ownership; Dividend Policy; and Leverage. Multiple linear regression tests with a 90% confidence level (p<0.1) were used to look at the data with SPSS software. The results of the study showed that corporate governance on the value of the company is influenced by the Independent Board of Commissioners (p = 0.079); institutional ownership (p = 0.000); and dividend policy (p = 0.000), but not affected by leverage (p = 0.223). Hence, suppose a company wants to have good corporate governance and increase the value of the company. In that case, it needs to pay attention to the most important things, like the Board of Independent Commissioners, institutional ownership, and dividend policy.